1994
DOI: 10.1002/cber.19941270704
|View full text |Cite
|
Sign up to set email alerts
|

Chelat‐stabilisierte 1,3‐Bis(acyloxy)‐1,3‐diethyldiboroxane aus Triethylboroxin und Carbonsäureanhydriden

Abstract: Chelate-Stabilized 1,3-Bis(acyloxy)-1,3-diethyldiboroxanes from Triethylboroxin and Carboxylic Acid Anhydrides['"]Triethylboroxin (A) reacts with carboxylic acid anhydrides (RC0)20 [R = Me: la; Et: lb; tBu: Id; Ph: l e ] with various rates to give high yields of the 3,7-dialkyl-lV5-diethyl-4,8,9trioxa-2,6-dioxonia-1,5-diboratabicyclo[ 3.3.l]nona-2,6-dienes dB(Et)OC(R)Ok(Et)OC(R)O (2) [R = Me: 2a (X-ray crystal structure analysis); Et: 2b; tBu: 2d; Ph: 2e], presumably via the unstable compounds bB(Et)OB(Et)OC(R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…6 ) which is structurally related to analogous complexes reported elsewhere. 22 Interestingly, in a separate NMR reaction, addition of an excess of phenylacetic acid to boronic acid 8c , in the presence of 5 Å MS shifted the equilibrium even further towards the “ate”-complex as seen by 11 B NMR (see further examples in the ESI † ).…”
Section: Resultsmentioning
confidence: 93%
“…6 ) which is structurally related to analogous complexes reported elsewhere. 22 Interestingly, in a separate NMR reaction, addition of an excess of phenylacetic acid to boronic acid 8c , in the presence of 5 Å MS shifted the equilibrium even further towards the “ate”-complex as seen by 11 B NMR (see further examples in the ESI † ).…”
Section: Resultsmentioning
confidence: 93%
“…for the borane adducts 14a, b; the FC term becomes small in the case of the borate 13 and changes its sign in the borates 3a, b. The situation for the FC contribution to the coupling constants 1 J( 17 O, 13 C) for all sp 3 -hybridized carbon atoms [36b] is similar to that for 1 J( 17 O, 11 B) in the borane adducts 14a, b. The PSO contribution can be of either sign, and cannot be neglected as is evident in the case of 13.…”
Section: Calculation Of Indirect Nuclear Spin-spin Coupling Constantsmentioning
confidence: 99%
“…In addition to routinely applied 1 H and 13 C NMR spectroscopy, many boronoxygen compounds have been studied extensively by 11 B NMR [1,2], allowing to distinguish readily between three-and four-coordinate boron atoms, and revealing information on equilibria and also on the nature of other substituents at the boron atom. Few studies have been carried out on boron-oxygen compounds focusing on 17 O NMR at natural abundance in solution [3 -5], and it has been shown that the chemical shifts δ 17 O cover a rather large range (ca.…”
Section: Introductionmentioning
confidence: 99%
“…2:1) (7). This demonstrates the presence of two types of boron compounds, presumably with tricoordinate (sp 2 ) and tetracoordinate (sp 3 ) environments [11]. The chemical shifts of around 32 ppm are indicative of a tricoordinate (sp 2 ) boron atom, although this value is shifted to high field compared with those reported in the literature [12]; on the other hand, the signals at ca.…”
Section: B Nmr Spectramentioning
confidence: 90%